Ritual da lua cheia: espiritualidade e tradição entre os Potiguara da Paraíba - Costa, Surama Santos Ismael da (2022)
This doctoral research aimed to study the Ritual da Lua Cheia, a ritual that has been performed since 2013, by the Potiguara shaman Isaias Guarapirá, at the village Lagoa do Mato located in Baía da Traição, in the State of Paraíba. The shaman reports that the Encantados, beings of light from the Potiguara cosmology, asked him in a dream, that he lead a pajelança for their people, on the first full moon day, inside the forest or near the force of the waters. The objective of this study was to develop a descriptive historical record of the ritual and understand it. Same brazilian indigenous people practiced pajelança, a ritual of healing and prophecy, in a significant and free way before the arrival of the colonizers. The moon was referenced and respected by them as something a kind of source of strength. With the convergence of symbolic and political horizons resulting from the historical relationships between indigenous people and missionaries, through cultural mediation, this practice was strongly affected and fought against. Over the time, pajelanças fell into disuse, in their genuine form or unfolded in other ritualistic forms influenced by cultural flows from different agents, such as Africans, giving rise, for example, to the Jurema Sagrada religiosity. This research fits the field of Empirical Sciences of Religion and uses an anthropological perspective in strong dialogue with Cultural and Oral History, anchored in authors such as Barcellos (2005), Brito (2020), Carvalho (2008), Cruz (2013, 2018), Grünewald (2008, 2020), Medeiros (2008), Miranda (2018), Pacheco de Oliveira (1998, 2004), Palitot (2005, 2020a, 2020b), Pompa (2003, 2011), Ramos (2015), Turner (1974, 1982, 1988, 1996), Csordas (2008) e Vilhena (2005). It is a study framed in the universe of the qualitative research. Also, an ethnographic inquiry that used participant observation and semi-structured interviews for purpose of data collection, and content analysis of oral and written narratives as technique for analyzing. As a result of the study, it was found that the Ritual da Lua Cheia is a healing ritual, a cultural performance that seeks an ethnic restitution of indigenous participants through reconnection with the past, recreating performing practices of the Pajelança Cabocla Juremeira. The jurema beverage is one of the “symbols of communion” with the past and the supernatural, used as a channel for mediumistic experiences linked to the Encantados beings and the spirits of caboclos, the proponents of cures together with the therapeutic effect of the beverage – a remedy for the body and for the soul. In its performance, we highlight the Toré, a ritualistic dance of the indigenous people which has religious and political nature. The Ritual da Lua Cheia can be seen as a ceremony in nature and an educational practice. As a contribution from this work, it is expected that the literary piece that emerged will serve as an instructional resource to the Potiguara community to give visibility to indigenous practices, promote the maintenance of the Potiguara culture and the resistance of its cosmology, and delivery knowledge to the scientific community interested in the religiosities present in the state of Paraíba.